PELATIHAN PEMBUATAN BIOPORI SEBAGAI PENANGGULANGAN BANJIR GENANGAN DI KECAMATAN PEUSANGAN KABUPATEN BIREUEN - Yayuk Kurnia Risna; Cut Azizah; Halus Satriawan; Ernawita Ernawita; Nuraina Nuraina (RAMBIDEUN : Jurnal Pengabdian Kepada Masyarakat, 2022)
The theme of community service is the application of biopore techniques in the yard of the Peusangan District Office, Bireuen Regency. This activity aims to reduce puddles caused by heavy rains and large amounts of water. Activities are carried out in 3 stages, namely preparation, implementation and reporting. The implementation method is done by lecture (question and answer) and demonstration. The results achieved from this service are (1) public understanding and awareness of the importance of keeping the environment clean, (2) application of biopore techniques to reduce waterlogging due to rain, and (3) creating a community that cares about the environment through biopori manufacturing activities. Sustainability of activities carried out with continuity by lecturers and students of the Masters Study Program in Natural Resources and Environmental Management Postgraduate Program at Al-Muslim University.